What you say and how you say it : Information disclosure in Latin American firms (2021)
Firms in Latin America could differentiate themselves by adopting better information disclosure practices. In this paper, we construct an Information Disclosure Index (IDI) for a sample of 454 firms in the six largest Latin America countries. We look at 4.622 company reports and show that firms with better disclosure practices have better market valuation (Tobin's Q) and better accounting financial performance (return on equity, ROE). We then measure the tone of the information disclosed using word content analysis and find that uncertainty in tone is negatively associated with firm valuation and accounting financial performance while a positive tone in corporate communications is positively associated with firm value and performance. This paper shows that the tone in corporate communications is as relevant as the amount of information disclosed to the market.